1982
DOI: 10.1148/radiology.143.3.7079503
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of gray-scale renal ultrasonography in differentiating cystic neoplasms from benign cysts.

Abstract: To evaluate the ability of gray-scale renal ultrasonography to distinguish cystic neoplasms from benign cysts, 182 cysts or cyst-like masses were reviewed retrospectively by three radiologists with varying degrees of experience in nephrosonography. All cases were proved by needle puncture or surgery. An unequivocal diagnosis of "cyst" based solely on ultrasonography was 98% accurate, with 2% being due to hematomas, localized hydronephrosis, or septa within the cyst. No cystic neoplasms were mistaken for benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(7 citation statements)
references
References 0 publications
1
4
0
2
Order By: Relevance
“…According to Taylor et al [7], CT is better than ultrasonography for detecting ACDK in long term dialysis patients, and CT has some margin of superi ority over ultrasonography in detecting small solid renal masses as well. However, Frohmiiller et al [ 15] suggested that ultrasonography appears to be more effective in the evaluation of the T stage of renal tumors compared to CT. No cystic neoplasms were mistaken for benign cysts by ultrasonography [16]. Our results confirm that ultraso nography is an effective method for the detection of renal cancer in patients on dialysis therapy.…”
Section: Discussionsupporting
confidence: 76%
“…According to Taylor et al [7], CT is better than ultrasonography for detecting ACDK in long term dialysis patients, and CT has some margin of superi ority over ultrasonography in detecting small solid renal masses as well. However, Frohmiiller et al [ 15] suggested that ultrasonography appears to be more effective in the evaluation of the T stage of renal tumors compared to CT. No cystic neoplasms were mistaken for benign cysts by ultrasonography [16]. Our results confirm that ultraso nography is an effective method for the detection of renal cancer in patients on dialysis therapy.…”
Section: Discussionsupporting
confidence: 76%
“…In fact, about 50% of patients above 50 years of age are expected to have at least one simple cortical cyst [1], In children, simple kidney cysts are relatively rare. Gordon et al [2] have documented only 9 cases of simple renal cysts during a period of 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…The pretest probability that a renal cyst is malignant depends, in part, on the radiologic appearance. Cysts are classified according to the Bosniak system . Most lesions are category 1 (benign); category 4 lesions are frankly malignant and are resected directly; and categories 2 and 3 are indeterminate.…”
Section: Pattern 9 Predominantly Cystic Lesionsmentioning
confidence: 99%